2014
DOI: 10.1016/j.orggeochem.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

High frequency floral changes at the Paleocene–Eocene boundary revealed by comparative biomarker and palynological studies

Abstract: The Cap d'Ailly area (Upper Normandy, France) shows several terrestrial-lagoonal sections recording the negative Carbon Isotope Excursion (CIE) associated with the Paleocene-Eocene Thermal Maximum (PETM; 55.8 Ma). A study of the biomarkers and spores/pollen content of the Vasterival section gave complementary information on paleofloral changes that occurred around the PaleoceneEocene (P-E) boundary. Aliphatic hydrocarbon fractions revealed a high abundance of vascular plant biomarkers, including tricyclic dite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…Similar correlations were observed in a more mature terrestrial set of samples (Garel et al, 2014). In a large set of immature marine and lacustrine samples, matching G 13 C values of both compounds evidenced a diagenetic relationship or a common source in (Sinninghe-Damsté et al, 2014).…”
Section: Processes Driving the Hopene And Triterpene Spatial And Tempsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar correlations were observed in a more mature terrestrial set of samples (Garel et al, 2014). In a large set of immature marine and lacustrine samples, matching G 13 C values of both compounds evidenced a diagenetic relationship or a common source in (Sinninghe-Damsté et al, 2014).…”
Section: Processes Driving the Hopene And Triterpene Spatial And Tempsupporting
confidence: 74%
“…The biological sources of the dominant triterpenes in the lobe sediments, hop-17(21)-ene, EE-hopane and diploptene (hop-22(29)-ene) are microorganisms and ferns (Douka et al, 2001;Innes et al, 1997Innes et al, , 1998Pattituci et al, 1995;Rohmer et al, 1984;Rohmer, 1993;Rontani and Volkman 2005;Sinninghe-Damsté et al, 2014;Welander et al, 2010). They are dominant triterpenes in terrestrial environments with low maturity of the organic matter (Garel et al, 2014). Their predominance in the Congo River sediments suggests that the export of land particles to the lobe complex is a significant source of these triterpenes ( Figure 6).…”
Section: Processes Driving the Hopene And Triterpene Spatial And Tempmentioning
confidence: 99%
“…It is also affected by the degree of leaf-water transpiration and soil-water evaporation that depend on climatic parameters, and by interspecific variability, which is linked to the plant physiology and biochemistry (Smith and Freeman, 2006). However, previous studies on the paleovegetation of the Cap d'Ailly area revealed no correlation between vegetation changes and n-alkane δ 2 H values, implying that the latter are mostly linked to paleoclimatic changes and not to changes in vegetation (Garel et al, 2014;Garel-Laurin, 2013). Furthermore, Garel et al (2013) produced δ 2 H values of onocerane I, a biomarker considered specific to a limited number of angiosperm species (Jacob et al, 2004).…”
Section: Factors Controlling Terrestrial N-alkane δ 2 H Valuesmentioning
confidence: 96%
“…For instance, macroscopic charcoal is usually transported only a few 100 m to a few kilometers and is thus mostly a local fire proxy (Whitlock and Larsen, 2001), whereas levoglucosan can be transported as an aerosol hundreds of kilometers and is therefore a regional to hemispheric fire proxy (Zennaro et al, 2014). The opposite is true for pollen and plant biomarker, with pollen having a larger catchment area than biomarker (e.g., Jansen et al, 2013;Garel et al, 2014).…”
Section: Quantitative Representativenessmentioning
confidence: 99%
“…Paleoenvironmental records based on biomarker distribution and/or isotopic composition have been produced from a variety of archives, such as peat cores (e.g., Pancost et al, 2002), lake sediment cores (e.g., Jacob et al, 2008a;Simonneau et al, 2013), loess (e.g., Xie et al, 2002), and bat guano deposits (e.g., Wurster et al, 2010). These fossil molecules are resistant to biodegradation (e.g., Brocks and Summons, 2004), surviving passage through the digestive systems of animals largely unchanged, and travel through the Earth system for thousands to millions of years (e.g., Eglinton and Calvin, 1967;Brocks and Pearson, 2005;Garel et al, 2014). The most specific biomarkers have recently become powerful tools to trace human activities such as land-use (e.g., Fisher et al, 2003;Jacob et al, 2008a;Lavrieux et al, 2013;Simonneau et al, 2013;Guillemot et al, 2015), and are reviewed here.…”
Section: Introductionmentioning
confidence: 99%